Choosing the Right Visual for Social Media: Comparing the Engagement of Stock Photos Versus Natural Photos: AEC783/WC444, 12/2023 - Zagonel, Anissa; Baker, Lauri M.; Shellhouse, Jarred; Boyer, Cheryl; Peterson, Hikaru; Morrison, Aly (EDIS, 2023)
Social media is an important piece of Extension outreach efforts. Across many different platforms, photos or graphics accompanying social media posts have repeatedly yielded greater results, in terms of engagement and success. Thus, it is imperative to include a visual element with each post, and a social media post without one would be considered a missed opportunity. This article explores the question of whether stock images are as effective as natural images. Facebook posts from the Center for Rural Enterprise Engagement (CREE) team were analyzed to determine differences in engagement rates for stock images and natural images taken by the CREE team. Results indicate natural photos had significantly higher engagement rates than stock photos. Thus, it is recommended that content creators strive to create and use their own photos for posts. However, because the difference between mean engagement rates for stock and natural photos was low, in times of need, a stock photo can produce better engagement than no photo at all.